Строение раковин ископаемых вивипарусов Украины - Даценко, Людмила Миколаївна; Даценко, Людмила Николаевна; Datsenko, Liudmyla (My University, 2008)
En: We have studied the microstructure of the wall of the shell of fossil viviparide by means of images of the electron microscope "JEOL Firms". Pictures of the structure of the wall of the last turn (with an increase from 30 to 5000) were obtained from Sinotaia barboti Sinz., Trochopaludina kimmeriana Dats., Tulotoma ovidii nasonis Bogatsch., Viviparus viviparus L.
The structure of the minerals of fossils of vyeparoses of Ukraine
Keywords: fossil viviparous; microstructure of the wall; crossed-fibrous structure; fibrous structure; строение раковин; вивипарусы Украины; строение стенки раковины; тонкий конхиолиновый слой